Barriers and requirements for adaptation of farmers in mountainous areas to climate change - Hossein jahantigh; Amir Bakhshi; Rezvan Ghorbani salkhord (تحقیقات کاربردی علوم جغرافیایی)
Identifying barriers and adaptation requirements is crucial for the successful implementation of climate change adaptation practices at the local level, especially in mountainous rural communities with limited local resources and technology. Due to the importance of this issue, in the present study, the barriers and requirements for adaptation to climate change in mountainous villages were investigated. The present research is descriptive-analytical in terms of purpose and method. The data collection tool was a questionnaire, free interview and observation of the researcher from the study area. The statistical population of rural households is Papi section of Khorramabad city (N = 2346). Using Cochranchr('39')s formula and sampling method, 330 households were selected as a sample. To analyze the data, descriptive statistics and exponential exploratory co-integration rank test (Johansen method) were used. The results showed that farmers in the mountainous villages of the study area face several adaptation barriers that are more serious institutional, normative, technological and information and cognitive barriers. Given that adaptation conditions are an important factor in reducing or eliminating adaptation barriers and improving farmerschr('39') adaptation capacity to climate change, local economic development, local infrastructure, production technology, and the granting of micro-credentials are the most prominent adaptation requirements in these were the grounds. In addition, due to the effective role of government, cooperatives and villagers themselves in rural development, a rational adaptation framework for selecting optimal adaptation strategies in cooperation with these three, as appropriate regional adaptation measures and policies for research proposals was presented.